Religious Multicultural Education as a Middle Path: Beyond Liberal Multiculturalism and Its Contribution to the SDGs in the Indonesian Muslim Majority Context - Wiranto, Erham Budi; Waston; Ali, Mohamad; Nirwana, Andri; Wachidi; Saif Uddin Ahmed Khondoker; Masruri, Siswanto (Profetika: Jurnal Studi Islam, 2026)
Objective:  Assess the limitations of the liberal and theological multicultural education paradigm and formulate an alternative framework that is able to bridge the two in the context of a majority Muslim society such as Indonesia. Theoretical framework: Integrating critical multicultural education with Religious Studies as a non-confessional, phenomenological, and dialogical approach that serves as a bridge between secular relativism and theological absolutism. Literature review: Based on an interdisciplinary literature review in multicultural education, religious education, and educational philosophy that highlights criticism of liberal and theological paradigms. Method: Using a qualitative approach with philosophical and conceptual design through literature studies and expert interviews to strengthen theoretical analysis. Results: The liberal paradigm tends to marginalize religion to the private sphere, while the theological paradigm is exclusive and less dialogical. Alternatively, Religious Multicultural Education is proposed as a middle ground approach that emphasizes epistemic plurality and interreligious dialogue. Implications: Contribute to the development of more inclusive education policies and curricula in a religiously plural society that faces tensions between secular and confessional models. Novelty: It lies in the synthesis between multicultural education and Religious Studies that produces a new model that is contextual, dialogical, and transcends the existing paradigm dichotomy.